Intestinal Anti-Inflammatory Activity of Baccharis dracunculifolia in the Trinitrobenzenesulphonic Acid Model of Rat Colitis - Cestari, Silvia Helena [UNESP]; Bastos, Jairo Kennup; Di Stasi, Luiz Claudio [UNESP] (Hindawi Publishing Corporation, 2011)
Baccharis dracunculifolia DC (Asteraceae) is a Brazilian medicinal plant popularly used for its antiulcer and anti-inflammatory properties. This plant is the main botanical source of Brazilian green propolis, a natural product incorporated into food and beverages to improve health. The present study aimed to investigate the chemical profile and intestinal anti-inflammatory activity of B. dracunculifolia extract on experimental ulcerative colitis induced by trinitrobenzenosulfonic acid (TNBS). Colonic damage was evaluated macroscopically and biochemically through its evaluation of glutathione content and its myeloperoxidase (MPO) and alkaline phosphatase activities. Additional in vitro experiments were performed in order to test the antioxidant activity by inhibition of induced lipid peroxidation in the rat brain membrane. Phytochemical analysis was performed by HPLC using authentic standards. The administration of plant extract (5 and 50 mgkg(-1)) significantly attenuated the colonic damage induced by TNBS as evidenced both macroscopically and biochemically. This beneficial effect can be associated with an improvement in the colonic oxidative status, since plant extract prevented glutathione depletion, inhibited lipid peroxidation and reduced MPO activity. Caffeic acid, p-coumaric acid, aromadendrin-4-O-methyl ether, 3-prenyl-p-coumaric acid, 3,5-diprenyl-p-coumaric acid and baccharin were detected in the plant extract.